PENGARUH KONSENTRASI DAN LAMA PERENDAMAN STEK LADA (Piper nigrum) DALAM LARUTAN ZAT PENGATUR TUMBUH (AUKSIN) - Teguh Supriyadi; Tyas Soemarah K.D; Endang Suprapti; Agus Budiyono (JURNAL ILMIAH AGRINECA, 2020)
The research entitled "The Effect of Concentration and Soaking Time of Pepper Cutters (Piper nigrum) in a Solution of Growth Regulatory Substances (auxin)" was carried out. Research was held on April – July 2020 in Green House of Agriculture Faculty, Tunas Pembangunan University, Jl. Balekambang Lor No. 1 Manahan, Surakarta. This study used a factorial experimental method based on a completely randomized design (CRD) consisting of 2 factors as treatment and 3 replications. The first factor, the concentration of growth regulators (auxin) (K), is divided into 3 levels, namely: 100 ppm (K1), 200 ppm (K2) and 300 ppm (K3); while the second factor, immersion time (P), also consists of 4 levels, namely: 2 hours (P1), 2.5 hours (P2), 3 hours (P3) and 3.5 hours (P4). The parameters observed in this study amounted to 9, with details as follows: Number of shoots, number of leaves, length of shoots, fresh and dry weight of shoots, number and length of roots, fresh weight and root dry weight. Based on the results of research on pepper cuttings due to the concentration of growth regulators (auxin) and the duration of immersion, the results showed that: Soaking time had a significant effect on the observed parameters, namely plant length in P2 treatment (2.5 hours). And it did not affect the parameters of the number of shoots, number of leaves, fresh and dry weight of shoots, number and length of roots, fresh weight and root dry weight.